New Evidence On The Urbanization of Global Poverty - Sangraula, Prem (The World Bank, 2007)
The authors provide new evidence on the extent to which absolute poverty has urbanized in the developing world, and the role that population urbanization has played in overall poverty reduction. They find that one-quarter of the world's consumption poor live in urban areas and that the proportion has been rising over time. By fostering economic growth, urbanization helped reduce absolute poverty in the aggregate but did little for urban poverty. Over 1993-2002, the count of the